THE EFFECT OF GRAPHIC ORGANIZER INSTRUCTION ON STUDENTS’ READING MOTIVATION - syafrizal (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
The aim of this study is to find out the effect of graphic organizer instruction on the students’ reading motivation. The study was done through quasi-experimental design. The data were collected using Motivation for Reading Questionnaire (MRQ) developed by Wigfield and Guthrie (1997) . The population consisted of 119 students. A cluster sampling technique was used to take them as samples. The samples were divided into two groups; experimental group and control group. Then, the data were analyzed using t-test and paired sample t-test methods to find out whether there was significant difference between the experimental group taught by graphic organizer instruction as the treatment and the control group taught conventionally. The results of the research shows that the significant probabilities were higher than 0.05 (>0.05) ) in both paired sample t-test and independent sample t-test. It meant that there was significant difference on the students’ reading motivation in the pre-questionnaire and in the post-questionnaire of the classes. In sum up, the the application of graphic organizer instruction gives positive effect toward the students’ reading motivation.